2021
DOI: 10.12968/jowc.2021.30.sup12.s6
|View full text |Cite
|
Sign up to set email alerts
|

A dual pressure indicator, two-layer compression system for treatment of venous leg ulcers: a review

Abstract: Objective: Venous leg ulcers (VLUs) are considered the most frequent category of hard-to-heal limb ulcers. Although evidence-based care of VLUs suggests that compression therapy plays a pivotal role in the standard of care, patient adherence is considered low, with at least 33% non-compliance, either due to perceived problems from clinicians regarding their own competency in applying the bandages, or from the patient finding the wrapping bothersome. For many years, four-layer bandaging has been considered the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Following our treatment protocol and wound healing at the 3‐ and 6‐month intervals, we also showed significantly higher EQ‐5D‐5L perfect health states at the respective follow‐up periods. The above findings are not surprising, as both VLU and the use of compression therapy are associated with significant pain 10,37 …”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Following our treatment protocol and wound healing at the 3‐ and 6‐month intervals, we also showed significantly higher EQ‐5D‐5L perfect health states at the respective follow‐up periods. The above findings are not surprising, as both VLU and the use of compression therapy are associated with significant pain 10,37 …”
Section: Discussionmentioning
confidence: 92%
“…The above findings are not surprising, as both VLU and the use of compression therapy are associated with significant pain. 10,37 Our study has its strengths. First, this is a large prospective study using our Chronic Wounds Registry on the longitudinal outcomes of patients with VLU in the Asian population, which is scarce in the current literature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While recent evidence showed that 2LB has similar healing outcomes compared to 4LB, 11,12 other advantages of 2LB over 4LB have been described. 2LB has been reported to be more tolerable as it is less bulky 11,12 . To add on, pain has been reported to be the most important factor impairing the QOL in patients with VLU 34,35 .…”
Section: Discussionmentioning
confidence: 99%